Sınıf Öğretmeni Adaylarının Pandemi Dönemindeki Bilişim Etiklerinin Belirlenmesi / Determining the Information Ethics of Prospective Primary School Teachers During the Pandemic Period - Bozkurt, Eyüp; Saripolat, Ayşegül (Disiplinlerarası Eğitim ve Araştırma Derneği, 2024)
Etik insanların çevresiyle olan tüm ilişkilerinin temelini oluşturan toplumsal değerleri, kuralları iyi-kötü, doğru-yanlış gibi ahlaksal açıdan araştıran, toplumsal-bireysel her türlü tercihi belirleyen ilkeler olarak yaşamın içerisindedir. Yaşamımıza teknolojinin dâhil olmasıyla beraber toplumun belirli değişimleri kaçınılmaz olmuştur. Teknolojinin gelişmesi sanayileşmeyi başlatmış ve bu sanayi toplumu hızla bilgi-iletişim teknolojilerinin önde olduğu bilişim toplumunu ortaya çıkarmıştır. Teknolojinin hayatımıza girmesi bazı problemleri beraberinde getirmiş ve etik kavramı bu noktada önemini hissettirmiştir. Global bir sorun olup 2019’un sonlarında ortaya çıkan Covid-19(Coronavirus) salgını önemli değişimlere sebep olmuştur. Bu değişimlerden en çok eğitim alanı etkilenmiş ve bu olumsuz etkilenmeyi azaltmak amacıyla uzaktan eğitim sistemleri kurulmuştur. İnsanlar böylelikle teknolojiyi daha fazla kullanmaya başlamışlardır. Burada en önemli etken bilişim etiğine uyulması ve etik kazanımıdır. Bu noktada sınıf öğretmenlerine önemli sorumluluklar düşmektedir. Bu araştırmada sınıf öğretmeni adaylarının bilişim etiklerinin cinsiyete, yaşa, sınıf düzeyine, internet erişim olanağına, internete erişim sağladığı araca, bilgisayara sahip olma durumuna ve internette harcanan süre aralıklarına göre farklılaşma olup olmadığını incelemek amaç edinilmiştir. Araştırmamız nicel araştırma yöntemlerinden genel tarama modelinde hazırlanmıştır. Araştırmada Duymaz (2014) tarafından geliştirilen “Gerçek Yaşam Durum Senaryolarıyla Bilişim Etiği Ölçeği” kullanılmıştır. Ölçek 4 senaryo ve her senaryoda 17 madde olmak üzere toplam 68 maddeden oluşmuştur. Araştırma sonucunda cinsiyete göre 4 senaryoda da anlamlı farklılık görülmüştür. Yaşa göre senaryo 1 ve 2’de anlamlı bir farklılık görülürken, senaryo 3 ve 4’de anlamlı farklılık görülmemiştir. Sınıf düzeyine göre Senaryo 1, 2 ve 3’de anlamlı farklılık görülmemişken, Senaryo 4’de anlamlı bir farklılık görülmüştür.

Ethics, as principles that shape all societal and individual choices, are deeply embedded in life by examining social values and norms from a moral perspective, such as good-bad or right-wrong. With the integration of technology into our lives, significant societal transformations have become inevitable. The development of technology initiated industrialization, which rapidly transitioned into an information society dominated by information and communication technologies. The incorporation of technology into daily life has brought certain challenges, highlighting the importance of the concept of ethics. A global issue, the Covid-19 (Coronavirus) pandemic, which emerged at the end of 2019, has caused significant changes. Among these, the field of education was most affected. To mitigate the negative impacts, remote education systems were implemented, leading people to use technology more frequently. At this point, adherence to information ethics and the acquisition of ethical principles became critical. Class teachers hold significant responsibilities in this regard. This study aims to examine whether the information ethics of prospective primary school teachers differ based on gender, age, grade level, internet access opportunities, the devices used for internet access, ownership of a computer, and the duration spent online. The study was designed using the general survey model, one of the quantitative research methods. The "Information Ethics Scale with Real-Life Scenario Applications," developed by Duymaz (2014), was used as the research instrument. The scale consists of four scenarios, with each scenario comprising 17 items, resulting in a total of 68 items. The findings of the study revealed significant differences across all four scenarios based on gender. Regarding age, significant differences were observed in Scenarios 1 and 2, but no significant differences were found in Scenarios 3 and 4. Based on grade level, no significant differences were detected in Scenarios 1, 2, and 3, whereas a significant difference was observed in Scenario 4. These results underscore the varying dynamics of information ethics among prospective primary school teachers, influenced by demographic and technological factors.
Determining the Information Ethics of Prospective Primary School Teachers During the Pandemic Period
Keywords: Educational Psychology; Eğitim Psikolojisi